+0  
 
0
102
1
avatar

The roots of the equation 2x^2 - 5x - 4 = 2x + 3 can be written in the form x = (m±sqrt n)/p, where m, n, and p are positive integers with a greatest common divisor of 1. What is the value of n?

 Dec 15, 2021
 #1
avatar+23186 
+1

2x2 - 5x - 4  =  2x + 3     --->     2x2 - 7x - 7  =  0

 

Using the quadratic formula with  a = 7  b = -7  and  c = -7:

x  =  [ - -7  +/-  sqrt( (-7)2 - 4(2)(-7) ) ]  /  [ (2)(2)

 

x  =  [ 7  +/-  sqrt(105) ]  /  4 

 Dec 15, 2021

9 Online Users

avatar